Broadband Lumped Mirror Array mmWave Antenna for Wireless and Defense Systems - Manish Varun Yadav; Lanston Pramith Fernandes; Swati Varun Yadav; Tanweer Ali; Dinesh Yadav; Vikas Singh; Kirti Panwar bhati (Journal of Electrical and Computer Engineering)
This article introduces a novel lumped mirror array mmWave antenna designed for multiband microwave applications, including 5G, satellite communication, and defense systems. The antenna operates over a broad frequency range from 4.7 to 67.63 GHz, offering excellent impedance bandwidth of 70.4%. Developed on an FR-4 substrate with dimensions of 160 × 70 × 1.5 mm3, the design has been thoroughly validated through simulations in CST Microwave Studio. The proposed antenna achieves a reflection coefficient of −35 dB, ensuring minimal signal reflection. In addition, the antenna exhibits a high gain of 9.364 dBi and an efficiency of 89.5%, making it suitable for a wide range of applications, such as C-band, X-band, Ku-band, K-band, and Ka-band. The lumped mirror array design provides reliable polarization consistency across the entire operating frequency range, demonstrating its adaptability and effectiveness for next-generation wireless communication and defense systems.